Employee Performance Analysis: Compensation, Motivation, and Work Stress - Ikwan, Duril; Dewi, Dian Ayu Liana (The Graduate School of Sahid University, 2024)
The success of a business enterprise cannot be separated from the role of employees. Employee welfare needs to be maintained to achieve company goals, namely the quality of the work of the employees themselves. The reason for conducting this study is to find out how compensation, work stress, and motivation have an impact on the performance of employees of PT Bintang Karya Laut Rembang. This study involved 194 employees of PT Bintang Karya Laut Rembang. The sample selection technique used proportional random sampling. This study activity used 70 respondents as samples, which were obtained using the Slovin formula. Data analysis was performed with multiple linear regression analysis. From this study, it was found that the compensation variable had a partial positive effect on the performance of employees of PT Bintang Karya Laut Rembang, the work motivation variable had a partial positive effect, and the work stress variable had a partial negative effect. Findings from the determination test show that compensation, work motivation, and work stress variables can contribute 83.5% of employee performance, while the remaining 16.5% is a factor not analyzed in this study.